Spotify’s effectiveness in improving 7th grade students’ pronunciation - Lucky Puput Hidayah; Yuliati (Universitas Negeri Semarang, 2025)
The ability to pronounce words correctly is a crucial component of learning a language for those seeking to acquire proficiency in the language. Proper pronunciation is essential for ensuring your message is clear and comprehensible to listeners. Many Indonesian students have problems pronouncing English words. It was found that the words are pronounced as they are written in the text. This is because Indonesian and English have different pronunciation systems. The objective of this study is the investigation of the effectiveness of using Spotify for the improvement of students’ pronunciation by means of the teaching of receptive skills. The use of Spotify, with its features to support receptive skills, was implemented by the researchers. The features include sound for listening and lyrics for reading. The approach of this research is an experimental study, which means that it is a research study that uses an experimental design and is typically done in a laboratory setting. An experimental study is a method used to investigate the effects of treatments under controlled conditions. The mean score of the pretest was 60.81, and the mean score of the posttest rose to 78.12 after using the Spotify application. The results show a marked improvement in pronunciation.